Introduction of Root Trainer Nursery Technology in Forestry Sector - Maharashtra - Khedkar, M. H.; Subramanian, K. (Indian Forester, 1996)
The Forest Development Corporation of Maharashtra Limited is one of the agencies implementing Rs.431.00 crore Maharashtra Forestry Projtect funded by the World Bank. The FDCM Ltd. Has to raise 1,25,000 ha under Production Forestry Component and 45,000 ha under Rehabilitation of Degraded Forests (RDF). A Nursery Development Unit has been created to introduce the Root trainer nursery technology. The FDCM Ltd. Through this unit has introduced the Root trainers in Iwo nursury sites namely at Lohara (Chandrapur District) and at makhmalabad (Nashik Distrct). As per the advice of Dr.J .P . Chandra. The 150 cm4 Block type Root traniners were procured and the planting stocks were raised. 3.91 lakhs of seedlings of Dalbergia sissoo, Bombax cerba, Acacia catechu, Bamboo, Gmelina arborea. Atlanthus,Tectona grandis etc. were planted over an area of 433.95 ha during 1995 monsoon . The details of the pioneering efforts in introducing the Root Trainer Nursery in the Forestry Sector in Mahnrashtra are briefly descrihed so that other states can adopt the technology.